Food niche overlap among neotropical frugivorous bats in Costa Rica - Lopez, Jorge E. (2006)
Food habits of 15 species of frugivorous bats were studied at La Selva Biological Station, Costa Rica. Eight hundred and fifty-four (854) fecal samples and 169 samples from fruit parts and seeds discarded by bats beneath feeding roosts were analyzed. During eight months of study, 47 fruit species consumed by bats were identified. Five plant genera (Cecropia, Ficus, Piper, Solanum, and Vismia) constituted 85% of all plants found in fecal samples. Feeding niche breadth differed significantly among the six most common species of frugivorous bats (Artibeus jamaicensis, Carollia sowelli, C. castanea, C. perspicillata, Dermanura sp., and Glossophaga commissarisi). All species, except for Dermanura sp., showed a diet dominated by one or two plant species. This suggests a pattern of resource partitioning at a generic level, in which Carollia consumed mainly Piper, Artibeus consumed Ficus and Cecropia, and Glossophaga consumed Vismia. Cluster analysis revealed higher values of food niche overlap in congeneric species than among species of different genera. Results show that if food is a limiting factor, mechanisms other than trophic selection must reduce interspecific interference or competition for food in this frugivorous bat guild.